Recycling of polymeric materials - Muhammad Fyras Azlan (Nanyang Technological University, 2021)
For more than 50 years, global production and consumption of plastics have continued to rise. An estimated 381 million tonnes of plastics were produced in 2015, almost a 4% increase over 2014, contributing to an already apparent upward trend over the past few years. Plastic is versatile, lightweight, flexible, moisture-resistant, strong, and relatively inexpensive. Those are the attractive qualities that lead us to such a voracious appetite and over-consumption of plastic goods worldwide. However, most plastic products ultimately end up as waste with staying power due to their extremely durable nature and high resistance to decomposition. Our tremendous attraction to plastic, coupled with an undeniable behavioural propensity of increasingly over-consuming, discarding, littering and thus polluting, has become a combination of lethal nature. Plastic pollution is a growing global concern due to its many negative impacts on the environment. Landfills that are approaching total capacity, harmful gases released that pollute the atmosphere and microplastics found in the ocean are just a few of the many examples that plastic pollution has brought to the environment. Hence, the growing concern of increasing plastic production and consumption has led to many various global movements and efforts to reduce or at least slow them down. Some examples are, the global plastic straws movement, a ban on plastic bags in some countries and awareness campaigns to reduce the use of plastics. However, much more can be done to combat this worrying trend by promoting eco-friendly products as alternatives to plastics and coming up with new innovative ways to replace the many uses of plastics.